2015
DOI: 10.1021/acs.energyfuels.5b00486
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Methane Hydrate Dissociation under Different Backpressures

Abstract: Depressurization has been considered an economic and practicable method for natural gas hydrate (NGH) exploitation. To obtain the kinetic data of methane hydrate (MH) dissociation under different backpressures, MH dissociation by depressurization in a porous medium was investigated in situ using magnetic resonance imaging (MRI). MH was dissociated under backpressures that were varied from 2.8 to 2.2 MPa, and the hydrate saturation variation during dissociation was analyzed. One experimental case was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…In the series of depressurization experiments, the MH was dissociated with a constant back-pressure of 2.6 MPa in Case 1. Similar results were found by other researchers 21,23,44 and the results in Cases 2 to 8, the data suggested that the hydrate dissociation process using depressurization method can be divided into two main stages, hydrate dissociation begins several minutes later aer back-pressure decreased due to hydrate reformation and ice generation forming blockages in the porous medium. 2.…”
Section: Analysis Of the Hydrate Dissociation Characteristicssupporting
confidence: 89%
“…In the series of depressurization experiments, the MH was dissociated with a constant back-pressure of 2.6 MPa in Case 1. Similar results were found by other researchers 21,23,44 and the results in Cases 2 to 8, the data suggested that the hydrate dissociation process using depressurization method can be divided into two main stages, hydrate dissociation begins several minutes later aer back-pressure decreased due to hydrate reformation and ice generation forming blockages in the porous medium. 2.…”
Section: Analysis Of the Hydrate Dissociation Characteristicssupporting
confidence: 89%
“…They are effective methods to determine the water content in porous media using the cumulative amplitude of T 2 distribution (Ge et al, ; Kleinberg et al, ) and the signal intensity of magnetic resonance image (Wang et al, ; Zhao et al, ). In this study, both ends of the core sample were connect with bulk water during the permeability measurement.…”
Section: Methodsmentioning
confidence: 99%
“…image (Wang et al, 2015;Zhao et al, 2015). In this study, both ends of the core sample were connect with bulk water during the permeability measurement.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…For bulk MH characterization, techniques like magnetic resonance imaging (MRI) [102,103] are applicable, that can map 1 H non-invasively with a three-dimensional resolution. 1 H MRI produces images of hydrogen contained in liquids, but not in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 methane and solids like ice or MH because of their much shorter transverse relaxation times (T2) which produce a high contrast.…”
Section: Experimental Characterizationmentioning
confidence: 99%